Novi Kolizej v ljubljani - Ažman Momirski, Lučka (Urbani izziv, 2005)
The discussion about the New Kolizej in Ljubljana has been the core issue of architectural debate on the Slovene scene during the second half of 2004 and first half of 2005. During the discussion numerous issues were analysed (from the site to the quality of design) but not issues linked to culture and its development in the city, dealing with cultural issues in urbanism and the its effect on the city's public life. The hypothesis that the competition tender and competition proposals themselves aren't results of serious analyses of urban design in Ljubljana and furthermore that attempts are made to limit professional attention only to the city centre, instead of dealing with the issue in debates, analyses and trends as pertaining to the entire city, provestrue even with the problematic definition of programmes in the New Kolizej.
Keywords: Kolizej; kulturne ustanove; kulturno življenje; Ljubljana; mesta; urbani razvoj; urbanistično planiranje; zgradbe